2007
DOI: 10.1093/treephys/27.3.399
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related differences in leaf morphological and physiological responses in Hippophae rhamnoides along an altitudinal gradient

Abstract: In most woody plants, leaf morphological and physiological characteristics are extremely variable across environmental gradients, particularly across altitudinal gradients. Hippophae rhamnoides L., a dioecious and deciduous shrub species, occupies a wide range of habitats in the Wolong Nature Reserve, southwest China. We measured growth, sex ratio and morphological and physiological characteristics of leaves in male and female H. rhamnoides individuals along an altitudinal gradient. Shoot height (HT), leaf N c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
88
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(102 citation statements)
references
References 44 publications
12
88
1
1
Order By: Relevance
“…Previous studies documented that sexual dimorphisms result from different reproductive requirements of females and males, which cause sex-specific selection pressures, reduced survival of females under conditions with limited resources, unlike males with better tolerance to harsh environments (Barrett and Hough 2012). Therefore, the gender ratio is always biased to females under the favorable microhabitats and to males under unfavorable conditions (Dawson and Ehleringer 1993;Li et al 2007;Zhang et al 2009;Zhao et al 2012). The poplar was one of the representative pioneer genera during the succession processes.…”
Section: Sex-specific Difference Of Biomass Accumulation and Allocationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies documented that sexual dimorphisms result from different reproductive requirements of females and males, which cause sex-specific selection pressures, reduced survival of females under conditions with limited resources, unlike males with better tolerance to harsh environments (Barrett and Hough 2012). Therefore, the gender ratio is always biased to females under the favorable microhabitats and to males under unfavorable conditions (Dawson and Ehleringer 1993;Li et al 2007;Zhang et al 2009;Zhao et al 2012). The poplar was one of the representative pioneer genera during the succession processes.…”
Section: Sex-specific Difference Of Biomass Accumulation and Allocationmentioning
confidence: 99%
“…Females are generally more prone to sexual spatial segregation and more abundant in moist and resource-rich environments (Freeman et al 1976;Rowland and Johnson 2001;Hultine et al 2007). Sex niche partitioning results from the different tolerance levels to harsh stress (Xu et al 2008;Zhang et al 2010;Montesinos et al 2012) and different resource demands, such as water, light, and temperature (Dawson et al 2004;Li et al 2007;Xu et al 2008;Zhao et al 2009;Zhang et al 2010). The preference for different N forms may have a function in special segregation of the sexes.…”
Section: Introductionmentioning
confidence: 99%
“…Seabuckthorn has a wide distribution in various climate regions, as it is adapted to very diverse ecological conditions and demonstrates high level of resistance to various environmental stresses (Li et al , 2007. Previously, morphological, physiological, and biochemical traits of drought-stressed seabuckthorn have been studied (Li et al 2004;Yang et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, scavenging of free radicals/H 2 O 2 by the elevated level of antioxidant enzymes like SOD and catalase in response to cold stress occur maximum in first 12 h of cold exposure. Differences in physiochemical and growth characteristics in response to abiotic stress in different dioecious plants have been recorded earlier as well (Kumar et al 2006;Li et al 2005Li et al , 2007Wang and Griffin 2003), and in most of these studies female plants have been found more susceptible. In fact, females are more scarcely found in stressful environments compared to male members of the same plant species (Dawson and Ehleringer 1993).…”
Section: Resultsmentioning
confidence: 75%
“…Interestingly, reported male and female sex ratio in SBT is 2:3 (Huxley 1992), which is against the general behaviour of occurrence of dioecious species (Lloyd and Webb 1977). Morphological and physiological differences in response to cold stress between male and female plants have been investigated in several species (Kumar et al 2006;Li et al 2005Li et al , 2007. Plant response to cold acclimation is complex and diverse.…”
Section: Introductionmentioning
confidence: 99%